PENERAPAN METODE AHP SEBAGAI PENDUKUNG KEPUTUSAN PENETAPAN BEASISWA - Frieyadie, Frieyadie (Jurnal Pilar Nusa Mandiri, 2017)
Schools usually set the rules or criteria that must be met by the applicants for the scholarship. The problems faced by the school in the process of determining the establishment of scholarships including data collection process is conventionally frequent errors and the absence of clear criteria for students to receive a scholarship and is having trouble because of the scholarship applicants and the number of criteria used to determine the decision of recipients. The research objective to avoid errors in data collection, and better process again what if you have a lot of criteria, so as to obtain the results expected by the selectors' scholarship. AHP calculation results obtained priority criterion in the assessment of the Scholarship Selection. Where Achievement, Non-Academic Achievement, Income Parents, and Personality become a benchmark in the selection of the scholarship. The final results obtained from the selection of the scholarship by five experts that Student B is superior to 0.221 (22.1%) while the Student A 0.213 (21.3%), Student E 0.207 (20.7%), Student D 0.182 (18, 2%) and the Student C 0.176 (17.6%).